1990
DOI: 10.1037/0021-843x.99.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alcohol on psychophysiological hyperreactivity to nonaversive and aversive stimuli in men at high risk for alcoholism.

Abstract: Psychophysiological reactivity to nonaversive (1-KHz, 70-db tones) and aversive stimuli (shock) was examined in nonalcoholic men with multigenerational family histories (MFH) of alcoholism and family history negative (FH-) men, while sober and after consuming alcohol. In comparison with FH- Ss, sober MFH Ss had significantly larger skin conductance (SC) orienting responses (ORs), shorter OR latencies, slower habituation rates to the tones, and larger increases in heart rate and vasoconstriction to the shock. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
78
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(84 citation statements)
references
References 21 publications
5
78
0
1
Order By: Relevance
“…The observed group differences in the endocrine stress response are consistent with prior reports on autonomic parameters of response to aversive electric shocks and public speaking, where an increased stress-dampening effect of alcohol was found in high-risk subjects (Levenson et al, 1987;Finn et al, 1990;Conrod et al, 1998). In a recent study, Dai et al (2002) used a similar design as reported here to investigate HPA response to stress and alcohol in high-risk subjects.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The observed group differences in the endocrine stress response are consistent with prior reports on autonomic parameters of response to aversive electric shocks and public speaking, where an increased stress-dampening effect of alcohol was found in high-risk subjects (Levenson et al, 1987;Finn et al, 1990;Conrod et al, 1998). In a recent study, Dai et al (2002) used a similar design as reported here to investigate HPA response to stress and alcohol in high-risk subjects.…”
Section: Discussionsupporting
confidence: 89%
“…Levenson et al (1987) and Sinha et al (1998) found no alcohol effect on anxiety, per se, in a study of family history positive and negative subjects that employed a public speaking task, but did find that autonomic responses were dampened by alcohol. Other authors found that alcohol reduced anxiety, but during anticipation of electric shocks (Finn et al, 1990;Conrod et al, 1998). Thus, our timing to administer the subjective perceptions questionnaire after the TSST might have been inappropriate.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. FHN's [13,17,18,22,24,31,39,43,58,63]. Taken together these data suggest that individual differences in stress reactivity are associated with differences in sensitivity to EtOH's behavioral effects and vulnerability to alcoholism.…”
mentioning
confidence: 85%
“…Subjects that are family history positive (FHP) for alcoholism exhibit lesser sensitivity to certain behavioral effects of EtOH than family history negatives (FHN), due to increased acute functional tolerance to the drug's effects [42,52]. Furthermore, some studies find that FHP's have exaggerated autonomic and hypothalamic-pituitary-adrenal (HPA)-axis activation in response to stress or EtOH challenge, as compared to FHN's [13,17,18,22,24,31,39,43,58,63]. Taken together these data suggest that individual differences in stress reactivity are associated with differences in sensitivity to EtOH's behavioral effects and vulnerability to alcoholism.…”
mentioning
confidence: 99%